Respuesta :
If given
[tex] \lim_{x \to \ -9} (-x+8x+9)[/tex]
then
[tex]\lim_{x \to \ -9} (-x+8x+9)=-54.[/tex]
[tex] \lim_{x \to \ -9} (-x+8x+9)[/tex]
then
[tex]\lim_{x \to \ -9} (-x+8x+9)=-54.[/tex]
Following are the calculation to find the limit:
Given:
[tex]\lim_{x \to -9}\ (-x + 8 x + 9)[/tex]
To find:
value=?
Solution:
[tex]\lim_{x \to -9}\ (-x + 8 x + 9)[/tex]
applying the limit.
[tex]\to (-(-9) + 8 (-9) + 9)\\\\\to (+9 -72 + 9)\\\\\to -54[/tex]
Therefore, the final answer is "-54".
Learn more:
brainly.com/question/16850206